ECRANISATION OF SETTING IN ALWAYS AND FOREVER, LARA JEAN NOVEL INTO THE MOVIE - Wibawa, I Kadek Agus Ari; Aryani, I Gusti Agung Istri; Putra, I Komang Sumaryana (LITERA : Jurnal Bahasa Dan Sastra, 2025)
This study aimed to explain the changes in setting that occur in the ecranisation process of ‘Always and Forever’, Lara Jean novel into ‘To All the Boys: Always and Forever movie’. Moreover, this study was conducted by using a qualitative method. Document analysis and note-taking techniques were used in collecting data and then applied the ecranisation theory proposed by Eneste (1991) to analyze the data. The study results showed that the setting has undergone 37 reductions, eight additions, and seven variations. The changes that occurred during the adaptation are most likely because of the technical and time limitations of the movie production, the insignificance of the particular parts of the novel, and the importance of the particular part to be displayed in the movie.